1982
DOI: 10.1111/j.1600-0528.1982.tb00378.x
|View full text |Cite
|
Sign up to set email alerts
|

Differing profiles of periodontal disease in two similar South Pacific island populations

Abstract: The periodontal condition of a cross-section of individuals aged between 15-59 years was characterised from clinical and radiographic observations of dental calculus, gingival inflammation, the level of the gingival attachment , alveolar bone loss, teeth missing or requiring extraction for periodontal reasons. The common characteristics of the profile in Tonga and W. Samoa were a high prevalence of the factors common to periodontal disease: calculus and gingival inflammation; a progressive apical movement of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
9

Year Published

1990
1990
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 11 publications
3
45
1
9
Order By: Relevance
“…Prevalence of AP is higher among males (Beck et al 1987;Miller et al 1987) and non Whites (Kelly and Nikias et aI 1975) and those who smoke (Bergstrom 1989; Horning et aI 1992; Locker and Leake 1993) or have compromised health, e.g. diabetes Hugson et aI 1989;Emrich et aI 1993 International longitudinal and cross-sectional studies have shown that some populations (Cutress et al 1982;Africa et aI 1985) / individuals (LOe et al 1986) are apparently resistant to periodontitis despite exposure to abundant plaque and experiencing a high prevalence of gingivitis (Africa et al 1985). A 15-year longitudinal study of the natural history of periodontitis was conducted among a homogeneous, caries-free Sri Lankan population which had never experienced dentistry.…”
Section: Goalsmentioning
confidence: 99%
“…Prevalence of AP is higher among males (Beck et al 1987;Miller et al 1987) and non Whites (Kelly and Nikias et aI 1975) and those who smoke (Bergstrom 1989; Horning et aI 1992; Locker and Leake 1993) or have compromised health, e.g. diabetes Hugson et aI 1989;Emrich et aI 1993 International longitudinal and cross-sectional studies have shown that some populations (Cutress et al 1982;Africa et aI 1985) / individuals (LOe et al 1986) are apparently resistant to periodontitis despite exposure to abundant plaque and experiencing a high prevalence of gingivitis (Africa et al 1985). A 15-year longitudinal study of the natural history of periodontitis was conducted among a homogeneous, caries-free Sri Lankan population which had never experienced dentistry.…”
Section: Goalsmentioning
confidence: 99%
“…However, as a person attracts a fatal infection, and lives his last weeks or days, the microorganisms causing his death will be found in saliva, and therefore his post mortem dental calculus. Moreover, different people, in different locations on the globe, may have different bacteria specific to their oral floras (Cutress et al, 1982;Preus et al, 1995). If such different, specific bacteria are possible to find in different populations in our globalized society, it would undoubtedly be true for ancient cultures with no, or far less exchange of people, and thereby microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…This is certainly true for the present study group for whom dental services are non existent, attributable to socioeconomic conditions, and fear of mixing with members of other communities. [6,7] The use of saliva as a diagnostic fluid has become somewhat of a transitional success story during the last few decades. It is a complex biological fluid composed of enzymes, hormones, antibacterial constituents, electrolytes etc.…”
Section: Discussionmentioning
confidence: 99%
“…Results of studies on TAC Tulunoglu et al [9] Total antioxidant values were higher in caries active groups Uberos et al [13] Total antioxidant capacity of the saliva of patients with caries in deciduous teeth was greater than among those without caries Prabhakar et al [14] Total antioxidant capacity of saliva increased significantly in caries active children Hegde et al [15] Total antioxidant capacity of saliva increased in children with caries Preethi et al [10] Total antioxidant capacity of saliva increased in caries active children Kumar et al [16] TAC of saliva increased in children with Severe early childhood caries and increasing prevalence of dental caries predisposes to the increase in TAC of saliva Dodwad et al [1] Total antioxidant capacity of saliva increased significantly in cariesactive children when compared to caries-free children Hegde et al1 [7] TAC level increases with increase in severity of caries Ahmadi-Motamayel et al [18] TAC was significantly higher in the saliva of caries active group relative to the caries free subjects Mahjoub et al1 [9] TAC levels and salivary total protein increased in children with severe early childhood caries compared with caries-free children Pandey et al [20] Total antioxidants in saliva increased with caries activity Muchandi et al [21] Salivary TAC increases in patients with early childhood caries Silva et al [22] Salivary Total Antioxidant capacity was higher in children with early childhood caries as compared to caries free children …”
Section: Name Of the Authormentioning
confidence: 99%